PROBLEMS OF STUDY AND CONSERVATION OF FLORA BIODIVERSITY IN KAZAKHSTAN - Ryabushkina , N.; Abugalieva , S.; Turuspekov , Y. (Eurasian Journal of Applied Biotechnology, 2016)
Plants are vitally important part of biodiversity that determines a global stability of ecosystems. According to the International Convention on Biological Diversity, two thirds of plants in the world are underextinction due to anthropogenic activities and global climate change. The strategies of plant protection on regional and global levels must be focused on evaluation of current conditions of bioresources, the development of systematic statuses of all living plant species, including those under the extinction. There is a necessity to fullydescribe floristically rich regions with purpose to develop a proper strategies for conservation of ecosystems, rare, endemic, and industrially important wild species both in situ and ex situ. Based on international experience, the achievement of this goal should be achieved through creation ofprotected natural territories in Kazakhstan, including National Reserves and National Parks. One of the modern approaches for the integrated study of the plant genetic resources is molecular systematics, which is based on combination of research studies in botany and molecular genetics.